Studi Awal Karakteristik Pohon Sarang Dan Sarang Orangutan (Pongo pygmaeus pygmaeus : Linnaeus 1760) - Albertus Tjiu, Mochammad Khoetiem, Irwan Lovadi (Jurnal Protobiont, 2014)
Pongo pygmaeus pygmaeus constitutes one of Borneo orangutan subspecies. Orangutans are arboreal animals that utilitize twigs and branches to build a nest. Scientific informations related to subspecies P. p. pygmaeus are considered remarkably rare. The aim of this study was to determine the characteristics of P. p. pygmaeus nesting tree and nest. This study was conducted from April to July 2013, at Peninjau Hill, Kapuas Hulu. Data collection method used in this study was line transect method. The parameters observed were the height of nesting tree, nest height, nest position, nest class and the type of nesting tree. The nesting tree height of  P. p. pygmaeus in Peninjau Hill ranged from 5 m to 39 m with the nest hight ranged from     3 m – 37 m. Generally, the position of nest is at position 2 with nest class mostly in class 4. The nest height significantly corresponds to tree height. Nesting trees consist of 42 trees genera dominated by Santiria. Trees of Dipterocarpaceae family dominate as the nesting tree of orangutan in Peninjau Hill. As much as 46,53% of nesting tree of P. p. pygmaeus also serves as feeding tree.